Antenna Synthesis Through the Characteristics of Desired Amplitude - Andriychuk, Mykhaylo I. (Cambridge Scholars Publisher, 2019)
The book is devoted to the synthesis problems that arise in the theory and design of radiating systems (antennas). The characteristics of desired amplitude are data placed into a synthesis problem. A synthesis problem belongs to a class of inverse problems and its aim is to determine a distribution of current or fields in an antenna, which produces the amplitude radiation characteristic as close as possible to the desired one. Freedom of choice of phase distribution of the desired radiation pattern (RP) is used as an additional possibility of better approximation to such RPs. This book studies.